Preparation method and application of degradable conductive hydrogel

By preparing a mixed solution of silk fibroin and polymer solution, and adding conductive materials and crosslinking agents, a degradable conductive hydrogel is formed, which solves the problem of insufficient strength of the existing hydrogel, and realizes a hydrogel with both tensile and strength, suitable for wearable devices and other fields.

CN119875149APending Publication Date: 2025-04-25SHANGHAI INST OF MICROSYSTEM & INFORMATION TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411981309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing hydrogels molded with silk fibroin are limited in related fields due to their low strength.

Method used

Degradable conductive hydrogel is formed by preparing silk fibroin solutions and polymer solutions (such as polyvinyl alcohol solutions) and adding conductive materials and crosslinking agents to the mixed solution. This method adjusts the Young's modulus and conductivity of the hydrogel by adjusting the mass ratio of silk fibroin to polymer solution and the ratio of added conductive materials and crosslinking agents.

Benefits of technology

It has achieved a high tensile and strength of degradable conductive hydrogels, and is suitable for wearable devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875149A_ABST
    Figure CN119875149A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of microelectronics, in particular to a preparation method and application of degradable conductive hydrogel. According to the method, a silk fibroin solution and a macromolecule solution are prepared firstly, the macromolecule solution has biocompatibility, and the Young modulus of hydrogel prepared on the basis of the macromolecule solution is larger than that of hydrogel prepared on the basis of the silk fibroin solution; mixing the silk fibroin solution with the polymer solution; sequentially adding a conductive material and a cross-linking agent, and uniformly stirring and mixing to obtain a mixed solution; and putting the mixed solution into a mold, and curing to form the degradable conductive hydrogel. Therefore, the degradable conductive hydrogel has both stretchability and strength and can be better applied to the field of wearable equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of microelectronic technology, and in particular to a preparation method of a degradable conductive hydrogel and application thereof. Background Art

[0002] In recent years, as people pay more and more attention to medical health, wearable devices that can monitor various physiological parameters in real time at low cost and in a convenient way have developed rapidly. The progress of wearable devices has benefited from the emergence of various new flexible devices. In order to monitor human physiological information, these flexible devices must be soft enough and have a certain stretchability to achieve conformal adhesion with various irregular surfaces of human skin. On the other hand, they must have high biocompatibility. Hydrogels are widely used in some wearable devices because of their simple preparation, low cost and good biocompatibility. Conductive hydrogels are used as strain gauges to monitor changes in human posture because of their high stretchability and resistance changes with strain.

[0003] Silk fibroin is a biological protein material extracted from natural silk cocoons. It has high biocompatibility with the human body and has been certified by the U.S. Food and Drug Administration (FDA). At the same time, the mechanical properties of silk fibroin materials are adjustable, and it can be made into hard bone nails or flexible films. Under certain conditions, it can be controlled and degraded, making it an environmentally friendly material. Because it comes from natural silk cocoons, which can be obtained by silkworms spinning silk, it is also a renewable material. In recent years, silk fibroin materials have been widely studied and used in various scenarios related to the human body.

[0004] However, although the existing hydrogels formed by silk fibroin have good biocompatibility and flexibility, they have low strength, which limits their application in related fields. Summary of the invention

[0005] In order to solve the above technical problems, the present application discloses, on one hand, a method for preparing a degradable conductive hydrogel, which at least comprises the following steps:

[0006] preparing a silk fibroin solution and a polymer solution; the polymer solution is biocompatible, and the Young's modulus of a hydrogel prepared based on the polymer solution is greater than the Young's modulus of a hydrogel prepared based on the silk fibroin solution;

[0007] Mixing the silk fibroin solution with the polymer solution;

[0008] Adding a conductive material and a cross-linking agent in sequence, and stirring and mixing them evenly to obtain a mixed solution;

[0009] The mixed solution is placed in a mold and solidified to form a degradable conductive hydrogel.

[0010] In some feasible embodiments, the conductive material includes carbon nanotubes or ionic liquids; and the conductive properties of the degradable conductive hydrogel are adjusted by adding carbon nanotubes or ionic liquids of different masses to the mixed solution.

[0011] In some feasible embodiments, the degradability of the degradable conductive hydrogel is adjusted by adding a protease to the mixed solution.

[0012] In some feasible embodiments, the polymer solution includes a polyvinyl alcohol solution;

[0013] The cross-linking agent includes a phosphoric acid solution or a glutaraldehyde solution.

[0014] In some feasible embodiments, the mass fraction of the silk fibroin solution is 4 wt % to 7 wt %;

[0015] The mass fraction of the polymer solution is 9wt% to 11wt%;

[0016] The mass fraction of the cross-linking agent is 85wt% to 90wt%.

[0017] In some feasible implementations, the mass ratio of the silk fibroin solution and the polymer solution when mixed is 3:1 to 1:1.

[0018] In some feasible implementations, before sequentially adding the conductive material and the cross-linking agent, the method further comprises:

[0019] Add stabilizers; the stabilizers include calcium chloride and glycerol.

[0020] In some feasible embodiments, the mass fraction of calcium chloride in the mixed solution is 2wt% to 5wt%;

[0021] The mass fraction of the glycerol in the mixed solution is 5wt% to 10wt%.

[0022] On the other hand, the present application also discloses a degradable conductive hydrogel, which is prepared based on the above-mentioned preparation method.

[0023] In another aspect, the present application further discloses a flexible electronic device, which comprises the above-mentioned degradable conductive hydrogel.

[0024] The embodiment of the present application first prepares a silk fibroin solution and a polymer solution, wherein the polymer solution is biocompatible, and the Young's modulus of the hydrogel prepared based on the polymer solution is greater than the Young's modulus of the hydrogel prepared based on the silk fibroin solution; the silk fibroin solution and the polymer solution are mixed; a conductive material and a cross-linking agent are added in sequence, and stirred and mixed to obtain a mixed solution; the mixed solution is placed in a mold, and a degradable conductive hydrogel is formed after solidification. Thus, the degradable conductive hydrogel has both stretchability and strength, and is better applied in the field of wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 A schematic diagram of a process for preparing a degradable conductive hydrogel provided in an embodiment of the present application;

[0027] Figure 2 A schematic diagram of a cured degradable conductive hydrogel provided in an embodiment of the present application;

[0028] Figure 3 A schematic diagram of a degradable conductive hydrogel in a stretched state provided in an embodiment of the present application;

[0029] Figure 4 A stress-strain curve corresponding to a degradable conductive hydrogel provided in an embodiment of the present application;

[0030] Figure 5 The resistance change rate test result of a degradable conductive hydrogel provided in an embodiment of the present application;

[0031] Figure 6 This is a schematic diagram of a degradable conductive hydrogel before and after degradation provided in an embodiment of the present application. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present application. In the description of the present application, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "top", "bottom", etc. is based on the orientation or positional relationship shown in the accompanying drawings, which is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present application. In addition, the terms "first" and "second" are used only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may include one or more of the features explicitly or implicitly. Moreover, the terms "first", "second", etc. are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described here can be implemented in an order other than those illustrated or described here.

[0034] For the purpose of the following detailed description, it should be understood that the present invention may adopt various alternative changes and step sequences, unless expressly specified to the contrary. In addition, except in any operating examples, or otherwise indicated, all numbers representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values ​​that vary according to the desired performance to be obtained by the present invention. At least it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.

[0035] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0036] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. For example, a specified range from "1 to 10" should be considered to include any and all sub-ranges between a minimum of 1 and a maximum of 10. Exemplary sub-ranges of ranges 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.

[0037] See also Figure 1 , which is a schematic flow chart of a method for preparing a degradable conductive hydrogel provided in an embodiment of the present application. The method for preparing a degradable conductive hydrogel comprises at least the following steps:

[0038] S101: preparing a silk fibroin solution and a polymer solution; the polymer solution is biocompatible, and the Young's modulus of a hydrogel prepared based on the polymer solution is greater than the Young's modulus of a hydrogel prepared based on the silk fibroin solution.

[0039] The silk fibroin solution can be prepared by cutting the cocoons, degumming, washing, drying, dissolving, dialysis, centrifugation and other steps. Specifically, the preparation process of the silk fibroin solution includes:

[0040] Weighing dry and clean silk cocoons, placing them in a sodium carbonate solution, and performing a heating treatment to remove sericin from the cocoons, thereby completing degumming and forming silk.

[0041] For example, the silk cocoons can be cut into pieces and placed in a sodium carbonate solution for heating and stirring. The silk cocoons are silk cocoons after the pupae are removed. The sodium carbonate solution can be heated by an electric furnace or a pressure cooker, with a heating temperature of 60 to 100° C., a heating pressure of 0.5 to 1 MPa, and a heating time of 1 second to 1000 hours.

[0042] The silk is placed in deionized water and washed multiple times.

[0043] Exemplarily, the silk is washed by stirring washing or static soaking, wherein the stirring method of the stirring washing is mechanical stirring or magnetic stirring, and the magnetic stirring speed is 1 to 2000 r / min; during a single washing process, the mass ratio of the silk to the ultrapure water is 1:20 to 1:50, the unit is g / L, and the time is 60s to 5h; after each washing, the silk is taken out and squeezed dry, and the washing is repeated 1 to 50 times.

[0044] The washed silk is dried, and the dried silk is stirred and mixed with a lithium salt aqueous solution, and kept warm for a period of time to obtain a silk fibroin lithium salt aqueous solution.

[0045] Exemplarily, the drying treatment method is natural air drying or heating ventilation drying, the heating ventilation drying temperature is 50 to 70° C., and the drying time is 1 to 20 hours.

[0046] Exemplarily, the lithium salt aqueous solution is a lithium thiocyanate solution or a lithium bromide solution, and the concentration of the lithium salt aqueous solution is 0.01 to 2 g / ml; the insulation temperature is 30 to 80° C., and the insulation time is 0.5 to 5 h.

[0047] The use of lithium salt aqueous solution can break the hydrogen bond network within silk fibers, thereby dissolving the silk fibroin into a silk fibroin solution to generate new materials.

[0048] The silk fibroin lithium salt aqueous solution is poured into a dialysis bag and dialyzed in ultrapure water.

[0049] Exemplarily, the dialysis method is static dialysis or magnetic stirring dialysis. Optionally, the specification of the dialysis bag is 10-1000000Da, and the dialysis method is static dialysis or magnetic stirring dialysis; the stirring speed of the magnetic stirring dialysis is 1-2000r / min, the time interval for changing water during the dialysis process is 0.1-100h, and the volume of ultrapure water required for each dialysis is 1mL-1000L. After dialysis, the dissolved lithium bromide can be removed to prevent subsequent ion residues from causing harm to people.

[0050] Exemplarily, the stirring speed is 60 to 300 r / min, and the time interval for changing water during the dialysis process is 1 to 24 hours.

[0051] The dialyzed silk fibroin lithium salt aqueous solution is centrifuged, and the supernatant after centrifugation is collected to obtain the silk fibroin solution.

[0052] Exemplarily, the rotation speed of the centrifugal treatment is 10 to 20,000 r / min, the time is 6 s to 2 h, and the temperature is -3 to 5°C.

[0053] In some feasible implementations, the mass fraction of the silk fibroin solution is 4 wt % to 7 wt %. Specifically, the mass fraction of the silk fibroin solution may be 4 wt %, 5 wt %, 6 wt % or 7 wt %.

[0054] In the embodiment of the present application, the polymer solution can be a polyvinyl alcohol solution. Polyvinyl alcohol (PVA) is a synthetic polymer material, which also has high biocompatibility and is widely used in medical materials. Optionally, the mass fraction of the polyvinyl alcohol solution is 9wt% to 11wt%, and specifically, the mass fraction of the polyvinyl alcohol solution can be 9wt%, 9.5wt%, 10wt%, 10.5wt% or 11wt%. In other embodiments, the polymer solution can also be other polymer solutions, as long as it can generate a cross-linked network with a cross-linking agent, and can be interspersed with a silk fibroin cross-linked network to form a double network hydrogel, and the Young's modulus of the polymer hydrogel formed by the polymer solution is greater than the Young's modulus of the silk fibroin hydrogel.

[0055] The preparation process of the polymer solution may include: mixing the polymer particles with deionized water in a preset ratio, and specifically adding the polymer particles while stirring to improve the dissolution efficiency. In order to further increase the dissolution rate of the polymer particles, the polymer particles may be stirred under heating conditions, and the heating temperature may be 90°C to 120°C.

[0056] In the embodiment of the present application, the polymer solution may be a polyvinyl alcohol solution, and the polyvinyl alcohol particles and deionized water may be mixed in a mass ratio of 1:8 to 1:10 to obtain a polyvinyl alcohol solution with a mass fraction of 9 wt % to 11 wt %. Specifically, the mass ratio of the polyvinyl alcohol particles and the deionized water when mixed may be 1:8, 1:9 or 1:10.

[0057] S103: Mixing the silk fibroin solution and the polymer solution.

[0058] In some feasible embodiments, the mass ratio of the silk fibroin solution and the polymer solution when mixed is 3:1 to 1:1. Specifically, the mass ratio of the silk fibroin solution to the polymer solution can be 3:1, 2:1 or 1:1. In an embodiment of the present application, the polymer solution can be a polyvinyl alcohol solution, and the mass ratio of the silk fibroin solution to the polyvinyl alcohol solution can be 3:1, 2:1 or 1:1. By adjusting the mass ratio of the silk fibroin solution to the polymer solution, the Young's modulus and elongation at break of the conductive hydrogel can be adjusted. Exemplarily, by increasing the mass of the polymer solution in the mixed solution, the Young's modulus of the conductive hydrogel can be increased; conversely, by increasing the mass of the silk fibroin solution in the mixed solution, the elongation at break of the conductive hydrogel can be increased.

[0059] For example, when the mass ratio of the silk fibroin solution to the polyvinyl alcohol solution is 0:1, the Young's modulus of the hydrogel is 5.75 KPa, and the elongation at break is 220%; when the mass ratio of the silk fibroin solution to the polyvinyl alcohol solution is 1:3, the Young's modulus is 3.91 KPa, and the elongation at break is 380%. It can be further explained that the Young's modulus and elongation at break of the conductive hydrogel can be adjusted by adjusting the mass ratio of the silk fibroin solution to the polymer solution.

[0060] When the silk fibroin solution and the polymer solution are mixed, they can be gently stirred with a glass rod to prevent the generation of a large number of bubbles or the premature cross-linking of the silk fibroin due to violent stirring.

[0061] S105: Add the conductive material and the cross-linking agent in sequence, and stir and mix them evenly to obtain a mixed solution.

[0062] In some feasible embodiments, the cross-linking agent includes phosphoric acid solution or glutaraldehyde solution, etc. The cross-linking agent specifically includes two categories, one of which is a cross-linking agent that can produce electrolytes, such as phosphoric acid solution, phosphoric acid is a nonvolatile and decomposable inorganic acid, which is used as an acidulant in some foods, and an appropriate amount of phosphoric acid can be used as a cross-linking agent for PVA. Optionally, the mass fraction of the cross-linking agent is 85wt% to 90wt%. When it is mixed with the above-mentioned silk protein solution and polymer solution (such as polyvinyl alcohol solution), two hydroxyl groups of the phosphoric acid molecule will form a phosphodiester bond with two hydroxyl groups of polyvinyl alcohol, thereby forming a polyvinyl alcohol network, and the network formed by the curing and cross-linking of silk protein will be interspersed with the polyvinyl alcohol-phosphoric acid cross-linking network to form a double network hydrogel. Because phosphoric acid solution can produce electrolytes in aqueous solution, it can also be used as a conductive material, that is, step S105 can be described as: add phosphoric acid solution, and stir evenly to obtain a mixed solution. The other type is polymer cross-linking agents, which cannot produce electrolytes, such as glutaraldehyde solution, which can only promote the cross-linking of polymer solutions to form a network but will not produce electrolytes. Therefore, additional conductive materials need to be added to make the prepared hydrogel conductive so that it can be used in strain gauges.

[0063] Specifically, the mass of the phosphoric acid solution added to the mixed solution is 0.6 to 0.7 times that of the polyvinyl alcohol solution, such as 0.6, 0.65 or 0.7 times that of the polyvinyl alcohol solution. In step S105, when adding the crosslinking agent, slight stirring is required to mix the solutions evenly.

[0064] In some feasible embodiments, the conductive material includes carbon nanotubes or ionic liquids; the conductive properties of the degradable conductive hydrogel are adjusted by adding different masses of carbon nanotubes or ionic liquids to the mixed solution. In the embodiment of the present application, the conductive properties of the degradable hydrogel can be adjusted by adding carbon nanotubes to the mixed solution, and optionally, the mass fraction of the carbon nanotubes in the mixed solution is 1wt% to 5wt%. Specifically, the mass fraction of the carbon nanotubes in the mixed solution is 1wt%, 2wt%, 3wt%, 4wt% or 5wt%. In other embodiments, the conductive properties of the degradable hydrogel can be adjusted by adding ionic liquids to the mixed solution, and optionally, the mass fraction of the ionic liquid in the mixed solution is 1wt% to 10wt%. Specifically, the mass fraction of the ionic liquid in the mixed solution is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%.

[0065] In some feasible embodiments, the degradability of the degradable conductive hydrogel is adjusted by adding a protease to the mixed solution. Specifically, a protease can be added in step S105. Since the hydrogel contains silk fibroin, the degradation of the hydrogel can be triggered by adding the protease and activating the activity of the enzyme at high temperature. Optionally, the protease can be proteinase K, and the concentration of proteinase K can be specifically 0.05 mg / ml. The protease can be activated at a temperature of 50 to 60° C., thereby decomposing the silk fibroin and achieving the degradation of the hydrogel.

[0066] In some feasible embodiments, before the conductive material and the cross-linking agent are added in sequence, the method further includes: adding a stabilizer; the stabilizer includes calcium chloride and glycerol. By adding a stabilizer, the high and low temperature stability of the hydrogel can be improved. Among them, anhydrous calcium chloride can achieve the self-healing ability of the hydrogel, and its healing mechanism is: due to the presence of calcium chloride in the two broken hydrogels, calcium chloride can form a metal coordination bond with water molecules in the air, forming a chelation effect, and having the effect of "water absorption and expansion", which prompts the two sections of the hydrogel to contact together, form hydrogen bonds, connect into one and restore mechanical and electrical properties. And due to the hydrophilicity of calcium chloride, its high temperature resistance can be increased. Glycerol can be used as an antifreeze agent to achieve stable operation at a lower temperature. Among them, calcium chloride can be used as a high temperature stabilizer, and glycerol can be used as a low temperature stabilizer. In fact, the above two stabilizers are not limited to calcium chloride and glycerol. Without affecting the main performance of the hydrogel, other feasible high and low temperature stabilizers can also be selected.

[0067] In some feasible embodiments, the mass fraction of calcium chloride in the mixed solution is 2wt% to 5wt%; exemplary, the mass fraction of calcium chloride in the mixed solution is 2wt%, 3wt%, 4wt% or 5wt%. The mass fraction of glycerol in the mixed solution is 5wt% to 10wt%. Exemplary, the mass fraction of glycerol in the mixed solution is 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%.

[0068] S107: placing the mixed solution in a mold, and forming a degradable conductive hydrogel after solidification.

[0069] In the embodiment of the present application, the required volume of the mixed solution can be cast on the mold, and when the mixed solution is solidified, a degradable conductive hydrogel (such as Figure 2 Optionally, the curing conditions may be 20° C. to 25° C. and 35% to 50% relative humidity.

[0070] The embodiment of the present application can be prepared by mixing a silk fibroin solution prepared from natural silkworm cocoons with a polyvinyl alcohol solution, then adding anhydrous calcium chloride and glycerol, and after mixing evenly, adding a certain proportion of phosphoric acid as a cross-linking agent, stirring evenly, and curing in a mold to form a conductive ion hydrogel with both stretchability and strength. The prepared hydrogel can act as a strain gauge, and it can be attached to the hand joints or elbow joints of the human body for posture recognition.

[0071] On the other hand, the present application also discloses a degradable conductive hydrogel, which is prepared based on the above-mentioned preparation method.

[0072] For example, see Figure 3 The degradable conductive hydrogel (hereinafter referred to as hydrogel) prepared based on the above scheme can be subjected to a stretching test, wherein the mass ratio of the silk fibroin solution to the polyvinyl alcohol solution is 1:3, and the following can be obtained: Figure 4 The stress-strain curve shown can obtain the peak stress and strain values ​​corresponding to the hydrogel, and then solve for its corresponding Young's modulus of 3.91 kPa, and the elongation at break can reach 380%, which confirms that the hydrogel obtained based on this scheme has good tensile properties and strength.

[0073] The hydrogel was subjected to a stretching cycle test at a stretching rate of 50% to test its resistance change rate, and the following results were obtained: Figure 5 From the results shown, it can be seen that as the stretching cycle test proceeds, the conductive properties of the hydrogel (such as the resistance change rate) also fluctuate cyclically.

[0074] For example, see Figure 6By placing the hydrogel prepared according to this protocol in a 1 mg / ml proteinase K solution, when the time is t = 0 minutes, the hydrogel in the solution can be clearly seen (see Figure 6 Figure (a) shows that the product is completely degraded after t = 90 minutes. Figure 6 Figure (b) in the figure).

[0075] The present application further discloses a flexible electronic device in another aspect, which includes the above-mentioned degradable conductive hydrogel. Specifically, the flexible electronic device can be obtained by assembling the above-mentioned degradable conductive hydrogel with a wire. Exemplarily, the flexible electronic device can be a wearable strain sensor.

[0076] The above description is only an optional embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a degradable conductive hydrogel, characterized in that: At least the following steps are included: preparing a silk fibroin solution and a polymer solution; the polymer solution is biocompatible, and the Young's modulus of a hydrogel prepared based on the polymer solution is greater than the Young's modulus of a hydrogel prepared based on the silk fibroin solution; Mixing the silk fibroin solution with the polymer solution; Adding a conductive material and a cross-linking agent in sequence, and stirring and mixing them evenly to obtain a mixed solution; The mixed solution is placed in a mold and solidified to form a degradable conductive hydrogel.

2. The preparation method according to claim 1, characterized in that: The conductive material includes carbon nanotubes or ionic liquids; the conductive properties of the degradable conductive hydrogel are adjusted by adding carbon nanotubes or ionic liquids of different masses into the mixed solution.

3. The preparation method according to claim 1, characterized in that: The degradability of the degradable conductive hydrogel is adjusted by adding protease to the mixed solution.

4. The preparation method according to claim 1, characterized in that: The polymer solution includes a polyvinyl alcohol solution; The cross-linking agent includes a phosphoric acid solution or a glutaraldehyde solution.

5. The preparation method according to claim 4, characterized in that: The mass fraction of the silk fibroin solution is 4wt% to 7wt%; The mass fraction of the polymer solution is 9wt% to 11wt%; The mass fraction of the cross-linking agent is 85wt% to 90wt%.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the silk fibroin solution and the polymer solution when mixed is 3:1 to 1:

1.

7. The preparation method according to claim 1, characterized in that: Before sequentially adding the conductive material and the cross-linking agent, the method further comprises: Add stabilizers; the stabilizers include calcium chloride and glycerol.

8. The preparation method according to claim 7, characterized in that: The mass fraction of calcium chloride in the mixed solution is 2wt% to 5wt%; The mass fraction of the glycerol in the mixed solution is 5wt% to 10wt%.

9. A degradable conductive hydrogel, characterized in that: It is prepared based on the preparation method according to any one of claims 1 to 8.

10. A flexible electronic device, characterized in that: Comprising the degradable conductive hydrogel as claimed in claim 9.